IMPLEMENTATION OF MAXIMUM POWER POINT TRACKING TWO AXIS ON PHOTOVOLTAIC BASED ON ARDUINO UNO - Widodo; Ardiansyah, Luky (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
The photovoltaic system is a renewable energy source that utilizes solar energy and converts it into direct current (DC) electrical energy as an alternative energy to replace fossil fuels which will run out over time because it cannot be renewed quickly. In the design of the Maximum Power Point Tracking Two Axis On Photovoltaic Based on Arduino Uno intends to get a solar panel system that can work automatically following the maximum point of sunlight. The LDR (Light Dependent Resisitor) sensor functions to provide analog signals to Arduino Uno which Arduino Uno then processed as a basis for decision making to move the steper motor in changing the position of the solar panel so that it can get maximum sun exposure